A secure authentication scheme using locimetric and press touch code techniques - Noor Elya Afiqah, Che Nordin (2019)
A password is one of the most used access control procedures applied in virtually all digital and computing appliances. Generally, a password is a word or a string of characters used for user authentication to prove identity or access approval to gain access to a resource, which is to be kept secret from those not allowed access. The current existing password has some drawbacks such as smudge attack and shoulder surfing attack. Due to lower concern on user authentication, an Android based graphical authentication scheme is proposed in this research to solve the problem. Locimetric and the Malaysia map will be utilized in conjunction with the Press Touch Code. There are many techniques that have been proposed to overcome those limitations. For this research, we combine the Locimetric and Press Touch Code techniques to make the newly proposed authentication scheme is more secure. The purpose of this research is to design a secure hybrid authentication scheme using the two techniques mentioned above which is dependent to screen resolution size and test the effectiveness of the proposed authentication scheme on Android based operating system. From the literature review, we will discuss more details on the authentication scheme and the concept of Locimetric and Press Touch Code. Some part of the Passpoint Locimetric method together with the Press Touch Code and grid concept will be utilize in this research. This research consists of hardwares and softwares.